2023
DOI: 10.1038/s41598-023-27740-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different fillers on thermal conductivity, tribological properties of Polyamide 6

Abstract: An influence of different filler types and filler content on the thermal and abrasive wear properties of polyamide-6 is investigated. Al2O3, MgO, two glass powders with different SiO2 contents, and natural zeolite powder were selected as fillers. The fillers individually were added to the polymer matrix in proportions of 50 and 70% by weight. A hybrid filler-containing composite was created by mixing PA6/70 wt% MgO and PA6/80 wt% zeolite. The results show that the thermal conductive enhancement factor is highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 53 publications
1
3
0
1
Order By: Relevance
“…Our analysis determined that the aligned composite with 4 vol% filler exhibited a similar or higher thermal conductivity than that of composites with a filler content of 10 vol% or higher. Additionally, the aligned composites with a similar filler content (approximately 12 vol%) were considerably superior (>100%) to previously reported MgO composites (Figure 4e) [31][32][33][34][35][36]. Therefore, the obtained results verified that the proposed technique of manufacturing TIM composites can be an outstanding method for obtaining high-performance thermal pads compared with previously reported MgO polymer composites.…”
Section: Resultssupporting
confidence: 79%
“…Our analysis determined that the aligned composite with 4 vol% filler exhibited a similar or higher thermal conductivity than that of composites with a filler content of 10 vol% or higher. Additionally, the aligned composites with a similar filler content (approximately 12 vol%) were considerably superior (>100%) to previously reported MgO composites (Figure 4e) [31][32][33][34][35][36]. Therefore, the obtained results verified that the proposed technique of manufacturing TIM composites can be an outstanding method for obtaining high-performance thermal pads compared with previously reported MgO polymer composites.…”
Section: Resultssupporting
confidence: 79%
“…In a study conducted on MgO and Al 2 O 3 -filled polymer matrix composites, it was observed that MgO filler was more successful in enhancing wear resistance compared to Al 2 O 3 filler. 25 However, when the filler ratio was increased to 2.8 wt%, it was determined that the mass losses of all nanoparticle-filled composite materials were higher than that of the unfilled composite. Similar studies 26,27 have emphasized that exceeding a certain filler ratio in filled composite materials leads to agglomeration of filler particles within the composite structure, hindered homogeneous distribution, decreased interaction between matrix and filler, and consequently, negatively affects wear resistance.…”
Section: Wear Test Resultsmentioning
confidence: 99%
“…This can be interpreted as the higher hardness of the MgO compound compared to CuO and its ability to form a better transfer film layer between the composite material and the abrasive ball, resulting in improved wear resistance of MgO‐filled composite. In a study conducted on MgO and Al 2 O 3 ‐filled polymer matrix composites, it was observed that MgO filler was more successful in enhancing wear resistance compared to Al 2 O 3 filler 25 . However, when the filler ratio was increased to 2.8 wt%, it was determined that the mass losses of all nanoparticle‐filled composite materials were higher than that of the unfilled composite.…”
Section: Resultsmentioning
confidence: 99%
“…Bu zorluğun üstesinden gelmek için birçok araştırmacı takviye edici katkı malzemeleri kullanarak PA6 polimerinin özelliklerini geliştirme çalışmaları yapmıştır. Polimer malzemelerin gerek mekanik, fiziksel veya termal özelliklerini geliştirmek gerekse tribolojik özelliklerini iyileştirmek için matris bünyesine takviye, dolgu ve katkı malzemeleri ilave edilebilmektedir [1][2][3][4][5][6]. Bu malzemelerin içerisinde cam elyaf (CE), diğer elyaf türlerine göre düşük maliyetli olması, üstün kimyasal dirence ve yüksek yalıtım özelliklerine sahip olmaması ve ayrıca kolay şekillendirme ve temin edilebilirlik gibi özellikleriyle en çok kullanılan ve tercih edilen elyaf türüdür [4][5]7].…”
Section: Introductionunclassified